Effects of mechanical operation-induced root injury on maize growth and yield - Hu, Hong; Gao, Junfeng; Wu, Jie; Mao, Yijing; Lu, Jingzhu; Li, Qingtao (International Journal of Agricultural and Biological Engineering, 2021)
A 2-year field experiment was conducted in 2015 and 2016 by using artificial root pruning to simulate mechanical root injury caused by agricultural machinery components and reveal its effects on maize growth and yield. Quasi-level orthogonal experimental design was employed to create orthogonal tables with four factors of interest, namely, pruning time (jointing stage, JS; big trumpet period, BTP), pruning method (unilateral pruning, UNP; bilateral pruning, BIP), pruning distance (5, 10, and 15 cm) and pruning depth (5, 10, and 15 cm). Results revealed that 1) maize growth was inhibited at the beginning of root pruning; 2) stem diameter (SD) and plant height (PHE) were smaller than those of the control check (CK) but exceeded the latter after 20 d of root pruning in JS; 3) SD and PHE were always smaller than those of the CK under root pruning in BTP; 4) T8 (BTP, BIP, 5 cm of pruning distance and 15 cm of pruning depth) can reach to a significant level (p < 0.01). The vertical distribution and total dry weight (TDW) of maize root in soil were affected by different root pruning treatments. When pruning in JS, the root ratio in 0-10 cm soil was 11.6% in T2 (JS, UNP, a pruning distance of 10 cm and pruning depth of 10 cm). When pruning in BTP, the root ratio of 10-20 cm soil layer increased by 15%. However, the TDW of maize decreased, the largest of which occurred in T8 at 53%. With the exception of a 0.43% increase in T3 (JS, UNP, 15 cm of pruning distance and 15 cm of pruning depth), the maize yield of all other treatments decreased compared with that of CK, and the largest reduction was in T8 at up to 19.1%. This finding suggests that a small pruning distance and a large pruning depth greatly influence the growth and yield of maize before and during pruning in BTP. The influence of BIP is greater than that of UNP. These results provide evidence for the effects of mechanical root injury on maize growth and yield and serve as a reference for the selection of mechanical topdressing parameters. Keywords: maize, root pruning, growth, grain yield, mechanical operation-induced injury DOI: 10.25165/j.ijabe.20211406.5079 Citation: Hu H, Gao J F, Wu J, Mao Y J, Lu J Z, Li Q T. Effects of mechanical operation-induced root injury on maize growth and yield. Int J Agric & Biol Eng, 2021; 14(6): 47–53.